Research on the Influence of the Formal Characteristics of EWOM on Consumers' Purchase Intention. Issue 6 (April 2020) - Zhao, Nian; Li, Xiaolin; Zhang, Linbin
Abstract: E-WOM has an increasingly important influence on consumers. Previous researches mostly focused on the influence of e-WOM information on consumers'affection and behavioral intention. From the perspective of formal characteristics of e-WOM, we establishean emotional path that influences consumers' willingness to behave. Through the data analysis by smart PLS3.0, the influence of the visibility and interactivity of e-WOM on consumer's emotional experience and purchase intention was verified, and the marketing management inspiration was finally obtained.